At læse efter generne - Houe, Ulf (K&K - Kultur og Klasse, 2014)
Literary Darwinism challenges mainstream literary scholars by claiming that literary phenomena can be explained by biological theory. The Darwinists claim that modern literary studies lack a solid scientific base and that this is due to the influence of the postmodernists. Rather than idle speculations about textual autopoiesis and the death of the author, literary scholars should adopt the methodologies of the natural sciences and thus produce real explanations.This essay argues that even though there is certainly much of so-called postmodernism that can be criticized and that modern literary studies lack a thorough debate about the nature of scientific inquiry, the study of literature remains fundamentally the study of text. Thus, text sets the criteria for proper scientific procedure and methodology in the field of literary studies.This is not to deny that man is the product of natural selection or that bodies and brains are the readers and writers of text. But these facts are but conditions of possibility. Knowledge of biological theory will only to a very limited extent give real explanations of literature and culture: in fact, such explanations are almost always trivial and thus incapable of producing new knowledge.Biology is not only ill suited to give us new insights; it cannot provide a scientific base. This is because in order to obtain objective knowledge of literary phenomena, the object of inquiry is not human nature but real text. Instead, we must look to intertextuality and constructivism to provide the criteria of proper science.